Therapeutic granulocyte and monocyte apheresis (GMA) for treatment refractory sarcoidosis: a pilot study of clinical effects and possible mechanisms of action. (24th July 2014) - Olsen, H H; Muratov, V; Cederlund, K; Lundahl, J; Eklund, A; Grunewald, J
Summary: Sarcoidosis is a systemic, inflammatory disorder, which in a proportion of patients runs a chronic progressive course despite immunosuppressive treatment. Therapeutic granulocyte and monocyte apheresis (GMA) has been shown to be an effective treatment option for other systemic inflammatory disorders, but has not yet been investigated in sarcoidosis. The aim of this study was to evaluate the response to GMA in sarcoidosis. Seven patients with sarcoidosis refractory to standard immunosuppressive therapy received 10 GMA sessions. All patients underwent chest X-ray, spirometry, a Chronic Respiratory Disease Questionnaire (CRQ-SAS), blood tests and bronchoscopy with bronchoalveolar lavage (BAL) before treatment and at 2–4 weeks and 3 months (except bronchoscopy) after the last treatment session. Bronchoalveolar lavage fluid (BALF) cell differential counts were recorded and T cells from blood and BALF were analysed for markers of activity, differentiation and T regulatory function. Compared to baseline, five of seven patients reported an improvement in dyspnoea score. In BALF there was an increase in the percentage of macrophages and a decrease in the percentage of lymphocytes and CD4 + /FoxP3 + T cells. Furthermore, the decrease in BALF CD4 + /FoxP3 + T cells correlated significantly with an improvement in dyspnoea score. In peripheral blood there was a statistically significant increase in the percentage of CD4 + /CD27 − T cells and a trend towards an initial increase in the percentage of CD4 + /FoxP3 + T cells, followed by a statistically significant decrease. The effects of GMA on regulatory T cells are consistent with those observed in other inflammatory disorders and could potentially translate into a clinical benefit.